The role of clustering in rural industrialization: A case study of the footwear industry in Wenzhou - Huang, Zuhui; Zhang, Xiaobo; Zhu, Yunwei (International Food Policy Research Institute, 2007)
Wenzhou used to be one of the poorest regions in eastern China. With limited arable land, poor road access to major cities, and little support from the upper level governments, this region seemed to lack all the conditions necessary for economic growth. However, over the past several decades Wenzhou has developed the most dynamic private sector in China, and has accordingly achieved one of the fastest growth rates. In particular, the footwear industry in Wenzhou has grown from a negligible market share to the largest in China. Here, we report a survey of 140 Wenzhou-based footwear enterprises of various scales, and use this information to examine the driving forces behind the dramatic rural industrial growth seen in this region. Our results show that clustering deepens the division of labor in the production process and makes it possible for small entrepreneurial firms to enter the industry by focusing on a narrowly defined stage of production. Therefore, Wenzhou represents an example of how clustering plays a significant role in helping fledgling rural industries overcome the growth constraints of capital and technology in the incipient stage of industrialization.